2020
DOI: 10.1177/1753193420926420
|View full text |Cite
|
Sign up to set email alerts
|

A cost-utility analysis of open A1 pulley release for the treatment of trigger finger

Abstract: The United Kingdom National Institute for Health and Care Excellence considers a procedure to be cost-effective if the cost per quality-adjusted life year gained falls below a threshold of £20,000–£30,000 (€22,600–33,900; US$24,600–$36,900). This study used cost per quality-adjusted life year methodology to determine the cost-utility ratio of A1 pulley release. Pre- and postoperative EuroQol 5 Dimensions 5 Likert scores were collected prospectively over 6 years from 192 patients. The median pre- and postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We have demonstrated that the local pathway in our department, which is reliant on readily available neurophysiology with a technician-led service, allows us to significantly reduce the number of new patient appointments required. Our pathway developed in this way because of the availability of local resources rather than any proven superiority of neurophysiology over USS (Stirling et al., 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that the local pathway in our department, which is reliant on readily available neurophysiology with a technician-led service, allows us to significantly reduce the number of new patient appointments required. Our pathway developed in this way because of the availability of local resources rather than any proven superiority of neurophysiology over USS (Stirling et al., 2020).…”
mentioning
confidence: 99%
“…This has led some to argue whether the value should be discounted with time, with 3% or 5% suggested as possible constant discounting values (Severens and Milne, 2004). Previously published cost utility analyses in this journal have incorporated the discounting principle to the calculation of cost per QALY (Stirling et al., 2020).…”
mentioning
confidence: 99%